(untitled) (Research, Society and Development, 2021)
The delimitation of geomorphological habitats provides the identification of areas with greater ecological relevance. The objective of this work was to define, using geotechnologies, the drainage network and fragments of the riparian forest in the upper Piranhas/PB sub-basin. The work was developed in stretches of the Piranhas River, starting at the São Gonçalo dam, close to the municipality of Sousa, Paraíba and following about 20km in the direction of the source of the river, located in the municipality of Bonito de Santa Fé. The images from the Sentinel 2 B satellites were used, the RGB composition (vegetation, water bodies and soil) was RGB: 4 - 3 - 2. The areas of permanent preservation of the sub-basin were designed, using the delimitation tool (Buffer). The map layouts were made using the QGIS software version 2.18.1. The cartographic data generated was given in the SIRGAS2000 datum reference system and in geographic coordinates. Locations were identified in which the strip intended for preservation suffered degradation, the environmental impacts are more evident as it moves away from the São Gonçalo Dam, in evidence the native vegetation suppression, replaced by small agriculture, pastures and housing construction. Points 1 and 3 met the largest number of individuals with open and dense vegetation, and points 2 and 4 with large areas of cultivation and pastures. There is a shortage of native vegetation due to inadequate use of the soil in some points of the Permanent Preservation Area in contrast to what is governed by the legislation.